A scratch-resistant BOPP matte film and preparation method thereof

By adding ethylene-octene block copolymer and microcrosslinked polypropylene to the upper surface extinction layer of the BOPP extinction film, the problem of easy trace or damage during transportation and coating is solved, and higher scratch resistance and extinction effect are achieved.

CN119283468BActive Publication Date: 2025-03-28GUANGDONG DECRO PACKAGE FILMS
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411822567.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-28
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The existing BOPP mastication films are easily left or damaged due to extrusion or displacement scratching during transportation and coating. Especially under dark background materials, the scratches are obvious, which affects the packaging effect.

Method used

8~14% ethylene-octene block copolymer and 6~10% microcrosslinked polypropylene are added to the upper surface extinction layer. The compression deformation performance and impact resistance of the material are improved by combining the hard and soft segments of the ethylene-octene block copolymer; the crosslinking network of microcrosslinked polypropylene increases the tensile strength and yield strength.

Benefits of technology

It significantly improves the scratch resistance of BOPP matte film, reduces scratches and damage caused by scratching on the film surface, and ensures the matte effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119283468B_ABST
    Figure CN119283468B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of matte films, and in particular to a scratch-resistant BOPP matte film and a preparation method thereof. A scratch-resistant BOPP matte film of the present invention comprises: an upper surface matte layer, an intermediate core layer and a lower surface layer arranged in sequence; the upper surface matte layer comprises a matte masterbatch, and the matte masterbatch comprises 28-50wt% copolymerized polypropylene, 8-14wt% ethylene-octene block copolymer, 6-10wt% micro-crosslinked polypropylene and 30-50wt% high-density polyethylene; the ethylene-octene block copolymer comprises a highly crystalline hard segment with a low octene content and an amorphous soft segment with a high octene content; the intermediate core layer comprises homopolymerized polypropylene; and the lower surface layer comprises a glossy surface layer or a matte layer. The synergistic effect of the ethylene-octene block copolymer and the micro-crosslinked polypropylene is utilized to improve the compression deformation performance and impact strength of the copolymerized polypropylene as well as the tensile strength and yield strength, reduce the indentation in the scratching and pressure application stage of the film surface and the scratches and damage generated in the sliding stage, improve the scratch resistance of the upper surface matte layer, and ensure the matte effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of matte films, in particular to a scratch-resistant BOPP matte film and a preparation method thereof. Background Art

[0002] BOPP matte film mainly achieves the matte effect by scattering light, which can improve the grade of printed outer packaging and is mainly used in paper-plastic composite or electronic packaging industry. Since the matte matte of matte film can give people a soft, stylish and elegant high-end feeling and eliminate eye fatigue, BOPP matte film is increasingly used in the packaging field.

[0003] In order to obtain a better matte effect, the matte layer of BOPP matte film is mainly composed of high-density polyethylene and copolymer polypropylene. In the matte masterbatch system, copolymer polypropylene is the continuous phase, and high-density polyethylene is the dispersed phase. According to the principle of soft-hard, high-density polyethylene (hard phase) is mostly coated by copolymer polypropylene (soft phase). The matte principle of matte film is that during the stretching process of the matte masterbatch, because the randomness of copolymer polypropylene is relatively high, the crystallization speed is slow, and the crystallization temperature is relatively low, copolymer polypropylene will exist as a sea phase; however, due to the high viscosity, high crystallization rate and high crystallinity of high-density polyethylene, high-density polyethylene exists as an island phase; during the film stretching process, when copolymer polypropylene is still in a relatively soft phase state, high-density polyethylene has completed part or most of the crystallization, and the crystallized high-density polyethylene becomes a hard phase. Under the external tensile force, the high-density polyethylene phase of the matte layer will protrude compared to the copolymer polypropylene soft phase during the stretching process, forming a rough and uneven island-shaped matte surface layer, thereby achieving the matte effect. High-density polyethylene serves as the island phase in the microscopic "island" morphology of the matte film, and the sea phase polypropylene will be coated on the high-density polyethylene. After biaxial stretching of the film, it will present an "island" structure at the microscopic level.

[0004] However, during the transportation, secondary slitting, and transportation after lamination, the upper surface matt layer of the existing BOPP matt film will easily leave marks when it is squeezed or scratched. In severe cases, the microscopic morphology of the original film surface is destroyed. The scratches are particularly obvious when laminating on a dark background material. The upper surface matt layer is obviously missing at the severely scratched position, which seriously affects the packaging effect of the BOPP matt film. Summary of the invention

[0005] Based on this, the purpose of the present invention is to provide a scratch-resistant BOPP matte film, by adding a certain proportion of ethylene-octene block copolymer and micro-cross-linked polypropylene in the upper surface matte layer, to solve the problem that the film surface of the upper surface matte layer of the BOPP matte film is easily marked when it is squeezed or scratched by the film surface, thereby improving the scratch resistance of the film and ensuring the matte effect.

[0006] A scratch-resistant BOPP matte film comprises an upper matte layer, an intermediate core layer and a lower surface layer arranged in sequence; the upper matte layer comprises a matte masterbatch, the matte masterbatch comprises 28-50wt% copolymerized polypropylene, 8-14wt% ethylene-octene block copolymer, 6-10wt% slightly cross-linked polypropylene and 30-50wt% high-density polyethylene; the ethylene-octene block copolymer comprises a hard segment with a low octene content and a soft segment with a high octene content; in the hard segment, ethylene accounts for 8 0wt%~90wt%, octene accounts for 10wt%~20wt%; in the soft segment, ethylene accounts for 20wt%~40wt%, and octene accounts for 60wt%~80wt%; in the ethylene-octene block copolymer, the hard segment accounts for 20wt%~40wt%, and the soft segment accounts for 60wt%~80wt%; the crosslinking degree of the slightly crosslinked polypropylene is 1~5%; the intermediate core layer includes homopolymer polypropylene; the lower surface layer includes a glossy layer or a matte layer.

[0007] Ethylene-octene block copolymers include ethylene-octene blocks (hard segments) with low octene content and ethylene-octene blocks (soft segments) with high octene content. The molecular chains of block copolymers are highly regular and show good compatibility with copolymerized polypropylene. The hard segments of ethylene-octene block copolymers have high crystallinity, which limits the slip deformation of copolymerized polypropylene molecular chains, improves compression modulus and deformation resistance, and reduces pressure indentation; in the hard segments, high ethylene content helps to form a crystalline region, giving the copolymers higher strength and other properties. The crystalline ethylene segments can be closely arranged to form a regular crystal structure, thereby improving the rigidity and mechanical properties of the material; the addition of octene is mainly to adjust the flexibility and toughness of the copolymer. An appropriate amount of octene can destroy the crystallinity of the ethylene segments and increase the flexibility of the molecular chains, so that the copolymer has better toughness and impact resistance while maintaining a certain strength, which can not only ensure that the material has a certain strength, but also improve its compression deformation performance and impact resistance. The soft segment of the ethylene-octene block copolymer has good flexibility and elasticity, which gives the material toughness and resilience when compressed, is conducive to shape recovery after the compression force is removed to reduce permanent deformation, and can evenly distribute stress and improve impact strength; and the soft segment of the ethylene-octene block copolymer can also increase the activity of the molecular chain, promote the material to deform and yield during impact, and reduce brittle fracture; in the soft segment, the high octene content can greatly increase the flexibility and disorder of the molecular chain, and the long branched chain structure of octene can effectively hinder the close stacking of the molecular chain and reduce the intermolecular force, thereby giving the soft segment excellent compression deformation performance and impact resistance; the ethylene segment plays a certain connecting and regulating role in it, and the lower ethylene content can further reduce the regularity of the segment and reduce the possibility of crystallization, so that the soft segment maintains a good amorphous state and flexibility, so that the soft segment has high flexibility while still having good compatibility and bonding with other parts such as the hard segment. In addition, the hard segment with low octene content has high crystallinity. After being added into the copolymerized polypropylene / high-density polyethylene system, its crystalline part interacts with the matrix crystal to enhance the extinction effect. The amorphous soft segment with high octene content has high molecular chain flexibility, which increases light scattering and improves the extinction effect. Limiting the hard segment ratio of ethylene-octene block copolymer to 20wt%~40wt% and the soft segment ratio to 60wt%~80wt% is conducive to maintaining the matting effect and melt processing fluidity. If the hard segment ratio in ethylene-octene block copolymer is less than 20wt%, the soft segment ratio is greater than 80wt%, the soft segment ratio is too high, and the hard segment ratio is too low, which is not conducive to the matting effect. When compressed, the molecular chain is easy to slip, the compression modulus is low, and the deformation is large. Due to the weak entanglement of the molecular chain, the impact strength is low and the scratch resistance is poor; if the hard segment ratio in ethylene-octene block copolymer is greater than 40wt%, and the soft segment ratio is less than 60wt%, the hard segment ratio is too high, and the soft segment ratio is too low. The hard segment plays a dominant role, and the crystal size is too large to easily lead to phase separation, which is not conducive to light scattering and leads to uneven matting. When the ethylene-octene block copolymer is added at less than 8wt%, the scratch resistance of the upper surface matting layer cannot be effectively improved.When the ethylene-octene block copolymer is added in an amount greater than 14wt%, on the one hand, the mutual entanglement with the copolymerized polypropylene molecular chain is increased, which is not conducive to the dispersion of high-density polyethylene in the copolymerized polypropylene, thereby affecting the matte effect; on the other hand, it may cause a significant increase in the melt viscosity of the matte masterbatch, which may make the processing process difficult, affect the fluidity and uniformity of the melt of the upper surface matte layer, and affect the processing into the film.

[0008] Cross-linking points are formed between the molecular chains of micro-cross-linked polypropylene, forming a cross-linking network. Physical connection points are formed between the molecular chains of micro-cross-linked polypropylene and copolymerized polypropylene, which can effectively transfer stress when subjected to tensile force, just like a "bridge" to make the molecular chains cooperate to resist external forces, improve tensile strength, and limit the slippage of molecular chains, which can enhance the toughness required by the material when stretched, avoid fracture due to local stress concentration, improve yield strength, enable it to withstand greater stress, reduce scratch formation and expansion, improve the material's scratch resistance, and reduce surface scratches. The cross-linking degree of the micro-cross-linked polypropylene is limited to 1-5%. If the cross-linking degree is greater than 5%, on the one hand, the molecular chain of the micro-cross-linked polypropylene is too rigid, the viscosity of the system is greatly increased, and the fluidity is significantly reduced, making the processing more difficult; when stretched, the activity of the molecular chain is limited, the flexibility and toughness are greatly reduced, and the stress is concentrated at the cross-linking point to reduce the tensile and yield strength; on the other hand, it is easy to cause the upper surface matte layer system to separate, making the crystal morphology complex and disordered, affecting light scattering, and making the film matte effect unstable and locally uneven. If the degree of crosslinking is less than 1%, the micro-crosslinked polypropylene has few crosslinking points, the molecular chain is free, and the entanglement with the copolymerized polypropylene molecular chain is weak during stretching, easy to slip and displace, unable to effectively transmit force, low tensile and yield strength, and easy to deform and break. When micro-crosslinked polypropylene is added at more than 10wt%, on the one hand, excessive micro-crosslinking limits the activity space of the polypropylene molecular chain and increases the steric hindrance. When stretched, the molecular chain is difficult to effectively orient and deform to disperse the stress, and too many crosslinking points will become stress concentration points. When subjected to tensile force, these parts are prone to be destroyed first, resulting in a decrease in tensile strength. The molecular chain cannot be properly deformed due to excessive constraints of crosslinking points, and it will be destroyed at lower stresses, resulting in a possible decrease in yield strength and brittle yield behavior. The film lacks toughness when yielding, and is prone to direct fracture or large-area cracks, which reduces the scratch resistance of the BOPP matte film; on the other hand, the fluidity of the matte layer will be greatly reduced, resulting in a significant increase in processing difficulty, requiring higher processing temperature and pressure, increasing energy consumption and cost, and prone to problems such as extrusion instability. The amount of micro-cross-linked polypropylene added is less than 6wt%, and the micro-cross-linking forms few connection points. Only a few molecular chains can work synergistically during stretching, which insufficiently restricts the slippage of the molecular chains, is not conducive to improving the yield strength of the material, and the overall scratch resistance is poor.

[0009] Furthermore, at 230° C. and a load of 2.16 kg, the melt index of the ethylene-octene block copolymer is 1 to 5 g / 10 min. Limiting the ethylene-octene block copolymer to the above melt index range is beneficial to maintaining the matte effect and melt processing fluidity.

[0010] Furthermore, the melt index of the micro-crosslinked polypropylene is 2-4 g / 10 min at 230° C. and a load of 2.16 kg. Controlling the melt index of the micro-crosslinked polypropylene within the above range is conducive to maintaining appropriate fluidity and matte effect of the upper surface matte layer.

[0011] Furthermore, the preparation method of the micro-crosslinked polypropylene is a peroxide crosslinking method, which specifically comprises the following steps: 98.5-99.4wt% copolymerized polypropylene, 0.5-1wt% peroxide crosslinking agent DCP and 0.1-0.5wt% antioxidant are fully mixed in a high-speed mixer, the mixed material is added to a twin-screw extruder, heated and melted, and then the micro-crosslinked polypropylene is obtained by strand drawing, cooling, drying, pelletizing, vibrating and screening, and packaging. The preparation method has a simple operation process, is easy to realize industrial production, and has a controllable crosslinking effect. The copolymerized polypropylene used to prepare the micro-crosslinked polypropylene is one or more of ethylene-propylene binary copolymerized polypropylene or ethylene-propylene-butylene terpolymer, and the melt index of the copolymerized polypropylene used to prepare the micro-crosslinked polypropylene is 6-12g / 10min at 230°C and a load of 2.16kg; the antioxidant is one or more of hindered phenolic antioxidants or hindered amine antioxidants.

[0012] Furthermore, the copolymerized polypropylene in the upper surface matte layer is one or more of ethylene-propylene binary copolymerized polypropylene or ethylene-propylene-butylene terpolymer; the melt index of the copolymerized polypropylene in the upper surface matte layer is 6-12 g / 10 min at 230° C. and a load of 2.16 kg; the melt index of the high-density polyethylene in the upper surface matte layer is 12-20 g / 10 min at 190° C. and a load of 21.6 kg.

[0013] Furthermore, the intermediate core layer further comprises 0.5-1 wt% of an antistatic agent masterbatch; the homopolymer polypropylene of the intermediate core layer has a melt index of 2-4 g / 10 min at 230° C. and a load of 2.16 kg.

[0014] Furthermore, the lower surface layer is a glossy layer comprising 99-99.5wt% homopolypropylene and 0.5-1wt% anti-blocking agent masterbatch or a matte layer comprising 52wt% copolymer polypropylene and 48wt% high-density polyethylene; at 230°C and a load of 2.16kg, the homopolypropylene melt index of the glossy layer is 2-4g / 10min.

[0015] Furthermore, the preparation method of the scratch-resistant BOPP matte film comprises the following steps: the raw materials of the upper surface matte layer, the middle core layer and the lower surface layer are weighed in a dry ratio and then added to each extruder, the raw materials of each layer are melted and plasticized in each extruder and then metered by a metering pump, and then merged at a T-die head according to different extruder flow channels to form a thick sheet, the thick sheet is extruded and then chilled and cast, and after the cast sheet is shaped, it first enters a longitudinal stretching zone for longitudinal stretching, and then enters a transverse stretching zone for transverse stretching, and after the biaxial stretching of the film is completed, trimming, corona, winding, aging treatment, and finally slitting and packaging to obtain a finished product.

[0016] Furthermore, the extrusion temperature of the upper surface matte layer is 230~255℃; the extruder temperature of the middle core layer and the lower surface layer is 250~260℃; the temperature of the T-die is 230~245℃, the temperature of the chilled roller is 30~35℃, the temperature of the longitudinal stretching preheating roller is between 128~145℃, the temperature of the longitudinal stretching zone is 120~135℃, the longitudinal stretching ratio is 4~5 times, the transverse stretching preheating temperature is 160~175℃, the temperature of the transverse stretching zone is 155~165℃, and the transverse stretching ratio is 7~9 times.

[0017] For better understanding and implementation, the present invention is described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a schematic structural diagram of the scratch-resistant BOPP matte film described in Examples 1 to 4 of the present invention and the BOPP matte film described in Comparative Examples 1 to 9. DETAILED DESCRIPTION

[0019] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the embodiments of the present application. It should be clear in the present application that the embodiments described are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the embodiments of the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the embodiments of the present application.

[0020] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the embodiments of the present application. The singular forms of "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.

[0021] Since copolymer polypropylene is relatively soft, the scratches of BOPP matte film are more likely to occur on the sea phase wrapped in the island phase, that is, the copolymer polypropylene phase. Therefore, when copolymer polypropylene is used as the surface material of the film, the film surface will be relatively soft, and the yield strength and tensile properties of the film surface will be poor. It will easily leave marks when it is squeezed or scratched by displacement, and in severe cases, the original microscopic morphology of the film surface will be destroyed, so the overall scratch resistance is poor.

[0022] The inventors have found that the scratches of BOPP matte film are more likely to occur on the sea phase (i.e., copolymerized polypropylene phase) wrapped in the island phase. Since copolymerized polypropylene is relatively soft, the film surface will be relatively soft, and the yield strength and tensile properties of the film surface are poor. When it is squeezed or scratched by displacement, it will easily leave marks, and in severe cases, the original microscopic morphology of the film surface will be destroyed, so the overall scratch resistance is poor. The following reasons are why BOPP matte film is prone to scratches and wear: First, during the pressure application stage, the surface of the matte film is impacted by external force. When the pressure exceeds its compressive yield strength and impact strength, elastic deformation occurs. When the pressure is released, indentations appear on the surface; second, the external force slides on the surface of the matte film, and the surface is subjected to external tensile force. The tensile strength and yield strength of the material itself are insufficient, cracks appear on the scratched surface, and the surface is worn. Therefore, the scratching process of BOPP matte film mainly covers the two key stages of pressure application and sliding. Therefore, the present invention provides a BOPP matte film by improving the component formula of the matte masterbatch in the upper surface matte layer, thereby improving the compression deformation performance and impact strength of copolymerized polypropylene, reducing the indentation in the pressure application stage, and at the same time improving the tensile strength and yield strength of copolymerized polypropylene, reducing the wear in the sliding stage, and improving the scratch resistance of the matte film surface.

[0023] A scratch-resistant BOPP matte film comprises an upper matte layer 1, an intermediate core layer 2 and a lower surface layer 3 arranged in sequence; the upper matte layer 1 comprises a matte masterbatch, the matte masterbatch comprises 28-50wt% copolymerized polypropylene, 8-14wt% ethylene-octene block copolymer, 6-10wt% micro-crosslinked polypropylene and 30-50wt% high-density polyethylene; the ethylene-octene block copolymer comprises a hard segment with a low octene content and a soft segment with a high octene content; in the hard segment, ethylene accounts for The proportion of ethylene in the soft segment is 20wt%~40wt%, and the proportion of octene is 60wt%~80wt%; the proportion of the hard segment in the ethylene-octene block copolymer is 20wt%~40wt%, and the proportion of the soft segment is 60wt%~80wt%; the crosslinking degree of the slightly crosslinked polypropylene is 1~5%; the intermediate core layer includes homopolymer polypropylene; and the lower surface layer includes a glossy layer or a matte layer.

[0024] Furthermore, at 230° C. and a load of 2.16 kg, the melt index of the ethylene-octene block copolymer is 1 to 5 g / 10 min.

[0025] Furthermore, at 230° C. and a load of 2.16 kg, the melt index of the slightly cross-linked polypropylene is 2-4 g / 10 min.

[0026] Furthermore, the preparation method of the micro-crosslinked polypropylene is a peroxide crosslinking method, which specifically comprises the following steps: 98.5-99.4wt% copolymerized polypropylene, 0.5%-1wt% peroxide crosslinking agent DCP and 0.1%-0.5wt% antioxidant are fully mixed in a high-speed mixer, the mixed materials are added to a twin-screw extruder, melt-extruded at a processing temperature of 200°C, and the micro-crosslinked polypropylene is obtained by strand drawing, cooling, drying, pelletizing, vibrating and sieving, and packaging. The copolymerized polypropylene used to prepare the micro-crosslinked polypropylene is one or more of ethylene-propylene binary copolymerized polypropylene or ethylene-propylene-butylene terpolymer, and the melt index of the copolymerized polypropylene used to prepare the micro-crosslinked polypropylene is 6-12g / 10min at 230°C and a load of 2.16kg; the antioxidant is one or more of hindered phenolic antioxidants or hindered amine antioxidants.

[0027] Furthermore, the copolymerized polypropylene in the upper surface matte layer 1 is one or more of ethylene-propylene binary copolymerized polypropylene or ethylene-propylene-butylene terpolymer; at 230° C. and a load of 2.16 kg, the melt index of the copolymerized polypropylene in the upper surface matte layer is 6 to 12 g / 10 min; at 190° C. and a load of 21.6 kg, the melt index of the high-density polyethylene in the upper surface matte layer is 12 to 20 g / 10 min.

[0028] Furthermore, the intermediate core layer 2 also includes 0.5-1wt% antistatic agent masterbatch; the homopolypropylene of the intermediate core layer 2 has a melt index of 2-4g / 10min at 230°C and a load of 2.16kg; the effective content of the antistatic agent in the antistatic agent masterbatch is 30-50wt%, and the carrier is homopolypropylene.

[0029] Furthermore, the lower surface layer 3 is a glossy layer comprising 99-99.5wt% homopolypropylene and 0.5-1wt% anti-blocking agent masterbatch or a matte layer comprising 52wt% copolymer polypropylene and 48wt% high-density polyethylene; at 230°C and a load of 2.16kg, the homopolypropylene melt index of the glossy layer is 2-4g / 10min; the effective content of the anti-blocking agent in the anti-blocking agent masterbatch is 6wt%, the anti-blocking agent is fumed silica, D50 is 4.5μm, and the carrier is homopolypropylene.

[0030] Furthermore, the method for preparing the matte masterbatch comprises the following steps:

[0031] (1) adding the copolymerized polypropylene, the high-density polyethylene, the slightly cross-linked polypropylene, and the ethylene-octene block copolymer in the matte masterbatch into a high-speed mixer and mixing them thoroughly;

[0032] (2) Feed the mixed material into the twin-screw extruder stably at a set flow rate, and control the extrusion temperature between 220 and 245°C for extrusion granulation;

[0033] (3) Extruding the tie rods, cooling, drying, pelletizing, vibrating and screening, and packaging to obtain the matte masterbatch.

[0034] Furthermore, the total thickness of the scratch-resistant BOPP matte film is 15-22 μm, the thickness of the upper surface matte layer is 1.5-2.2 μm, and the thickness of the lower surface layer is 0.7-0.9 μm.

[0035] Furthermore, the preparation method of the scratch-resistant BOPP matte film comprises the following steps: the raw materials of the upper surface matte layer, the middle core layer and the lower surface layer are weighed in a dry ratio and then added to each extruder, the raw materials of each layer are melted and plasticized in each extruder and then metered by a metering pump, and then merged at a T-die head according to different extruder flow channels to form a thick sheet, the thick sheet is extruded and then chilled and cast, and after the cast sheet is shaped, it first enters a longitudinal stretching zone for longitudinal stretching, and then enters a transverse stretching zone for transverse stretching, and after the biaxial stretching of the film is completed, trimming, corona treatment, winding, aging treatment, and finally slitting and packaging to obtain the finished product.

[0036] Furthermore, the extrusion temperature of the upper surface matte layer is 230~255℃; the extruder temperature of the middle core layer and the lower surface layer is 250~260℃; the temperature of the T-die is 230~245℃, the temperature of the chilled roller is 30~35℃, the temperature of the longitudinal stretching preheating roller is between 128~145℃, the temperature of the longitudinal stretching zone is 120~135℃, the longitudinal stretching ratio is 4~5 times, the transverse stretching preheating temperature is 160~175℃, the temperature of the transverse stretching zone is 155~165℃, and the transverse stretching ratio is 7~9 times.

[0037] The physical properties and test methods of the embodiments or comparative examples of the present invention are as follows:

[0038] Glossiness is measured according to GB / T 10003-2008 standard, using the 45° angle method;

[0039] The haze is measured according to GB / T 10003-2008 standard;

[0040] The scratch resistance test method is as follows: the equipment is an American standard printing abrasion resistance tester produced by Dongguan Lichuan Instrument Co., Ltd., model LC-103B. The test weight is two pounds, and the matte film to be tested is fixed on the bottom of the weight and the panel respectively, and the matte surface is rubbed back and forth in a semi-elliptical manner with the matte surface against the matte surface. The number of scratches is set to 30 times, and the scratching speed is 40 times / min. After scratching, the changes in the haze and glossiness of the corresponding area are tested.

[0041] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. The proportions in the following embodiments or comparative examples are all weight percentages, and the components and contents of each layer in the embodiments of the present invention and comparative examples are shown in Table 1 below.

[0042] Table 1

[0043]

[0044] The ingredients are as follows:

[0045] Homopolymer polypropylene in the middle core layer and the lower surface layer: melt index is 3 g / 10 min.

[0046] Copolymer polypropylene: ethylene-propylene binary copolymer polypropylene, melt index is 9g / 10min.

[0047] Antistatic agent masterbatch: The effective component is propylene glycol monostearate, the effective content is 40wt%, and the carrier is homopolymer polypropylene.

[0048] Anti-blocking agent masterbatch: fumed silica, D50 is 4.5 μm, and the carrier is homopolymer polypropylene.

[0049] In the following examples or comparative examples, the copolymer polypropylene used to prepare the slightly cross-linked polypropylene is ethylene-propylene binary copolymer polypropylene with a melt index of 9 g / 10 min, and the antioxidant is a hindered phenol antioxidant with a brand of 1010.

[0050] Example 1

[0051] This embodiment provides a scratch-resistant BOPP matte film, comprising an upper matte layer 1, an intermediate core layer 2 and a lower surface layer 3 arranged in sequence. The specific structure can be found in Figure 1 .

[0052] The method for preparing each layer of resin of the scratch-resistant BOPP matte film of this embodiment comprises the following steps:

[0053] Preparation of resin for the upper surface matte layer 1: 40wt% copolymerized polypropylene (melt index of 9g / 10min), 42wt% high-density polyethylene (melt index of 16g / 10min), 8wt% ethylene-octene block copolymer (melt index of 3g / 10min, hard segment of 20wt% (ethylene accounts for 80wt%, octene accounts for 20wt%), soft segment of 80wt% (ethylene accounts for 20wt%, octene accounts for 80wt%)), 10wt% slightly cross-linked polypropylene (melt index of 3g / 10min, cross-linking degree of 3%) are uniformly mixed to obtain the resin for the upper surface matte layer 1.

[0054] Preparation of the middle core layer 2 resin: 99.5 wt % homopolymer polypropylene (melt index is 3 g / 10 min) and 0.5 wt % antistatic agent masterbatch are uniformly mixed to obtain the middle core layer 2 resin.

[0055] Preparation of the resin for the lower surface layer 3: 99.5 wt% of homopolymer polypropylene (melt index is 3 g / 10 min) and 0.5 wt% of anti-blocking agent masterbatch are uniformly mixed to obtain the resin for the lower surface layer 3.

[0056] The method for preparing the scratch-resistant BOPP matte film of the present embodiment comprises the following steps:

[0057] The raw materials of each layer are added to each extruder after being weighed in a dry ratio, wherein the temperature of the extruders of the middle core layer 2 and the lower surface layer 3 is 250°C, and the temperature of the extruder of the upper surface matte layer 1 is 240°C. The raw materials of each layer are melted and plasticized in each extruder and then metered by a metering pump, and then enter different extruder flow channels to merge and extrude at a T-die head, and are cast into thick sheets through a chilled roller. After the thick sheet is extruded, it is chilled and cast. After the cast sheet is shaped, it first enters the longitudinal stretching zone for longitudinal stretching preheating, and then longitudinal stretching is performed. The longitudinal stretching multiple is 5 times, and the longitudinal stretching temperature is 125°C. After the longitudinal stretching is finalized, it enters the transverse stretching zone for transverse stretching preheating, and then transverse stretching is performed. The transverse stretching multiple is 8 times, and the transverse stretching temperature is 160°C. After the film is biaxially stretched, it is trimmed and trimmed, followed by corona treatment, winding, and aging treatment, and finally slitting and packaging to obtain the finished product.

[0058] The total thickness of the film is 20 µm, the thickness of the upper surface matte layer 1 is 1.6 µm, the thickness of the middle core layer 2 is 17.6 µm, and the thickness of the lower surface layer 3 is 0.8 µm.

[0059] Example 2

[0060] This embodiment provides a scratch-resistant BOPP matte film, comprising an upper matte layer 1, an intermediate core layer 2 and a lower surface layer 3 arranged in sequence. The specific structure can be found in Figure 1 .

[0061] The method for preparing each layer of resin of the scratch-resistant BOPP matte film of this embodiment comprises the following steps:

[0062] Preparation of resin for upper surface matte layer 1: 38wt% copolymerized polypropylene (melt index of 9g / 10min), 42wt% high-density polyethylene (melt index of 16g / 10min), 14wt% ethylene-octene block copolymer (melt index of 3g / 10min, hard segment of 40wt% (ethylene accounts for 90wt%, octene accounts for 10wt%), soft segment of 60wt% (ethylene accounts for 40wt%, octene accounts for 60wt%)), 6wt% slightly cross-linked polypropylene (melt index of 3g / 10min, cross-linking degree of 3%) are uniformly mixed to obtain the resin for the upper surface matte layer 1.

[0063] Preparation of the middle core layer 2 resin: 99.5 wt % homopolymer polypropylene (melt index is 3 g / 10 min) and 0.5 wt % antistatic agent masterbatch are uniformly mixed to obtain the middle core layer 2 resin.

[0064] Preparation of the resin for the lower surface layer 3: 99.5 wt% of homopolymer polypropylene (melt index is 3 g / 10 min) and 0.5 wt% of anti-blocking agent masterbatch are uniformly mixed to obtain the resin for the lower surface layer 3.

[0065] The preparation method of the scratch-resistant BOPP matte film of this embodiment is the same as that of Embodiment 1.

[0066] The total thickness of the film is 20 µm, the thickness of the upper surface matte layer 1 is 1.6 µm, the thickness of the middle core layer 2 is 17.6 µm, and the thickness of the lower surface layer 3 is 0.8 µm.

[0067] Example 3

[0068] This embodiment provides a scratch-resistant BOPP matte film, comprising an upper matte layer 1, an intermediate core layer 2 and a lower surface layer 3 arranged in sequence. The specific structure can be found in Figure 1 .

[0069] The method for preparing each layer of resin of the scratch-resistant BOPP matte film of this embodiment comprises the following steps:

[0070] Preparation of resin for the upper surface matte layer 1: 39wt% copolymerized polypropylene (melt index of 9g / 10min), 42wt% high-density polyethylene (melt index of 16g / 10min), 11wt% ethylene-octene block copolymer (melt index of 3g / 10min, hard segment of 30wt% (ethylene accounts for 85wt%, octene accounts for 15wt%), soft segment of 70wt% (ethylene accounts for 30wt%, octene accounts for 70wt%)), 8wt% slightly cross-linked polypropylene (melt index of 3g / 10min, cross-linking degree of 3%) are uniformly mixed to obtain the resin for the upper surface matte layer 1.

[0071] Preparation of the middle core layer 2 resin: 99.5 wt % homopolymer polypropylene (melt index is 3 g / 10 min) and 0.5 wt % antistatic agent masterbatch are uniformly mixed to obtain the middle core layer 2 resin.

[0072] Preparation of the resin for the lower surface layer 3: 99.5 wt% of homopolymer polypropylene (melt index is 3 g / 10 min) and 0.5 wt% of anti-blocking agent masterbatch are uniformly mixed to obtain the resin for the lower surface layer 3.

[0073] The preparation method of the scratch-resistant BOPP matte film of this embodiment is the same as that of Embodiment 1.

[0074] The total thickness of the film is 20 µm, the thickness of the upper surface matte layer 1 is 1.6 µm, the thickness of the middle core layer 2 is 17.6 µm, and the thickness of the lower surface layer 3 is 0.8 µm.

[0075] Example 4

[0076] This embodiment provides a scratch-resistant BOPP matte film, comprising an upper matte layer 1, an intermediate core layer 2 and a lower surface layer 3 arranged in sequence. The specific structure can be found in Figure 1 .

[0077] The method for preparing each layer of resin of the scratch-resistant BOPP matte film of this embodiment comprises the following steps:

[0078] Preparation of resin for the upper surface matte layer 1: 39wt% copolymerized polypropylene (melt index of 9g / 10min), 42wt% high-density polyethylene (melt index of 16g / 10min), 11wt% ethylene-octene block copolymer (melt index of 3g / 10min, hard segment of 30wt% (ethylene accounts for 85wt%, octene accounts for 15wt%), soft segment of 70wt% (ethylene accounts for 30wt%, octene accounts for 70wt%)), 8wt% slightly cross-linked polypropylene (melt index of 3g / 10min, cross-linking degree of 3%) are uniformly mixed to obtain the resin for the upper surface matte layer 1.

[0079] Preparation of the middle core layer 2 resin: 99.5 wt % homopolymer polypropylene (melt index is 3 g / 10 min) and 0.5 wt % antistatic agent masterbatch are uniformly mixed to obtain the middle core layer 2 resin.

[0080] Preparation of the resin for the lower surface layer 3: 52 wt% of copolymerized polypropylene (melt index is 9 g / 10 min) and 48 wt% of high-density polyethylene (melt index is 16 g / 10 min) are uniformly mixed to obtain the resin for the lower surface layer 3.

[0081] The preparation method of the scratch-resistant BOPP matte film of this embodiment is the same as that of Embodiment 1.

[0082] The total thickness of the film is 20 µm, the thickness of the upper surface matte layer 1 is 1.6 µm, the thickness of the middle core layer 2 is 17.6 µm, and the thickness of the lower surface layer 3 is 0.8 µm.

[0083] Comparative Example 1

[0084] This comparative example provides a BOPP matte film, comprising an upper matte layer 1, an intermediate core layer 2 and a lower surface layer 3 arranged in sequence. The specific structure can be referred to Figure 1 .

[0085] The preparation method of each layer of resin of the BOPP matte film of this comparative example comprises the following steps:

[0086] Preparation of resin for upper surface matte layer 1: 52 wt% copolymerized polypropylene (melt index is 9 g / 10 min) and 48 wt% high-density polyethylene (melt index is 16 g / 10 min) are uniformly mixed to obtain the resin for the upper surface matte layer.

[0087] Preparation of the middle core layer 2 resin: 99.5 wt % homopolymer polypropylene (melt index is 3 g / 10 min) and 0.5 wt % antistatic agent masterbatch are uniformly mixed to obtain the core layer resin.

[0088] Preparation of the resin for the lower surface layer 3: 99.5 wt % of homopolymer polypropylene (melt index is 3 g / 10 min) and 0.5 wt % of anti-blocking agent masterbatch are uniformly mixed to obtain the resin for the lower surface layer.

[0089] The preparation method of the BOPP matte film of this comparative example is the same as the preparation method of the scratch-resistant BOPP matte film of Example 1.

[0090] The total thickness of the film is 20 µm, the thickness of the upper surface matte layer 1 is 1.6 µm, the thickness of the middle core layer 2 is 17.6 µm, and the thickness of the lower surface layer 3 is 0.8 µm.

[0091] Comparative Example 2

[0092] This comparative example provides a BOPP matte film, comprising an upper matte layer 1, an intermediate core layer 2 and a lower surface layer 3 arranged in sequence. The specific structure can be referred to Figure 1 .

[0093] The preparation method of each layer of resin of the BOPP matte film of this comparative example comprises the following steps:

[0094] Preparation of resin for the upper surface matte layer 1: 39wt% copolymerized polypropylene (melt index of 9g / 10min), 50wt% high-density polyethylene (melt index of 16g / 10min), and 11wt% ethylene-octene block copolymer (melt index of 3g / 10min, hard segment of 30wt% (ethylene accounts for 85wt%, octene accounts for 15wt%), and soft segment of 70wt% (ethylene accounts for 30wt%, octene accounts for 70wt%)) are uniformly mixed to obtain the resin for the upper surface matte layer.

[0095] Preparation of the middle core layer 2 resin: 99.5 wt % homopolymer polypropylene (melt index is 3 g / 10 min) and 0.5 wt % antistatic agent masterbatch are uniformly mixed to obtain the core layer resin.

[0096] Preparation of the resin for the lower surface layer 3: 99.5 wt % of homopolymer polypropylene (melt index is 3 g / 10 min) and 0.5 wt % of anti-blocking agent masterbatch are uniformly mixed to obtain the resin for the lower surface layer.

[0097] The preparation method of the BOPP matte film of this comparative example is the same as the preparation method of the scratch-resistant BOPP matte film of Example 1.

[0098] The total thickness of the film is 20 µm, the thickness of the upper surface matte layer 1 is 1.6 µm, the thickness of the middle core layer 2 is 17.6 µm, and the thickness of the lower surface layer 3 is 0.8 µm.

[0099] Comparative Example 3

[0100] This comparative example provides a BOPP matte film, comprising an upper matte layer 1, an intermediate core layer 2 and a lower surface layer 3 arranged in sequence. The specific structure can be referred to Figure 1 .

[0101] The preparation method of each layer of resin of the BOPP matte film of this comparative example comprises the following steps:

[0102] Preparation of resin for upper surface matte layer 1: 48wt% copolymerized polypropylene (melt index of 9g / 10min), 44wt% high-density polyethylene (melt index of 16g / 10min), and 8wt% slightly cross-linked polypropylene (melt index of 3g / 10min, cross-linking degree of 3%) are uniformly mixed to obtain the resin for the upper surface matte layer.

[0103] Preparation of the middle core layer 2 resin: 99.5 wt % homopolymer polypropylene (melt index is 3 g / 10 min) and 0.5 wt % antistatic agent masterbatch are uniformly mixed to obtain the core layer resin.

[0104] Preparation of the resin for the lower surface layer 3: 99.5 wt % of homopolymer polypropylene (melt index is 3 g / 10 min) and 0.5 wt % of anti-blocking agent masterbatch are uniformly mixed to obtain the resin for the lower surface layer.

[0105] The preparation method of the BOPP matte film of this comparative example is the same as the preparation method of the scratch-resistant BOPP matte film of Example 1.

[0106] The total thickness of the film is 20 µm, the thickness of the upper surface matte layer 1 is 1.6 µm, the thickness of the middle core layer 2 is 17.6 µm, and the thickness of the lower surface layer 3 is 0.8 µm.

[0107] Comparative Example 4

[0108] This comparative example provides a BOPP matte film, comprising an upper matte layer 1, an intermediate core layer 2 and a lower surface layer 3 arranged in sequence. The specific structure can be referred to Figure 1 .

[0109] The preparation method of each layer of resin of the BOPP matte film of this comparative example comprises the following steps:

[0110] Preparation of resin for the upper surface matte layer 1: 33wt% copolymerized polypropylene (melt index of 9g / 10min), 36wt% high-density polyethylene (melt index of 16g / 10min), 11wt% ethylene-octene block copolymer (melt index of 3g / 10min, hard segment of 30wt% (ethylene accounts for 85wt%, octene accounts for 15wt%), soft segment of 70wt% (ethylene accounts for 30wt%, octene accounts for 70wt%)), 20wt% slightly cross-linked polypropylene (melt index of 3g / 10min, cross-linking degree of 3%) are uniformly mixed to obtain the resin for the upper surface matte layer 1.

[0111] Preparation of the middle core layer 2 resin: 99.5 wt % homopolymer polypropylene (melt index is 3 g / 10 min) and 0.5 wt % antistatic agent masterbatch are uniformly mixed to obtain the core layer resin.

[0112] Preparation of the resin for the lower surface layer 3: 99.5 wt % of homopolymer polypropylene (melt index is 3 g / 10 min) and 0.5 wt % of anti-blocking agent masterbatch are uniformly mixed to obtain the resin for the lower surface layer.

[0113] The preparation method of the BOPP matte film of this comparative example is the same as the preparation method of the scratch-resistant BOPP matte film of Example 1.

[0114] The total thickness of the film is 20 µm, the thickness of the upper surface matte layer 1 is 1.6 µm, the thickness of the middle core layer 2 is 17.6 µm, and the thickness of the lower surface layer 3 is 0.8 µm.

[0115] In this comparative example, the melt viscosity of the matte masterbatch is greatly increased and the fluidity is significantly reduced, which makes the processing more difficult and the film is prone to breakage, affecting the smoothness of production and the matte effect of the matte film, and easily causing bright spots on the film surface.

[0116] Comparative Example 5

[0117] This comparative example provides a BOPP matte film, comprising an upper matte layer 1, an intermediate core layer 2 and a lower surface layer 3 arranged in sequence. The specific structure can be referred to Figure 1 .

[0118] The preparation method of each layer of resin of the BOPP matte film of this comparative example comprises the following steps:

[0119] Preparation of resin for the upper surface matte layer 1: 30wt% copolymerized polypropylene (melt index of 9g / 10min), 34wt% high-density polyethylene (melt index of 16g / 10min), 28wt% ethylene-octene block copolymer (melt index of 3g / 10min, hard segment of 30wt% (ethylene accounts for 85wt%, octene accounts for 15wt%), soft segment of 70wt% (ethylene accounts for 30wt%, octene accounts for 70wt%)), 8wt% slightly cross-linked polypropylene (melt index of 3g / 10min, cross-linking degree of 3%) are uniformly mixed to obtain the resin for the upper surface matte layer.

[0120] Preparation of the middle core layer 2 resin: 99.5 wt % homopolymer polypropylene (melt index is 3 g / 10 min) and 0.5 wt % antistatic agent masterbatch are uniformly mixed to obtain the core layer resin.

[0121] Preparation of the resin for the lower surface layer 3: 99.5 wt % of homopolymer polypropylene (melt index is 3 g / 10 min) and 0.5 wt % of anti-blocking agent masterbatch are uniformly mixed to obtain the resin for the lower surface layer.

[0122] The preparation method of the BOPP matte film of this comparative example is the same as the preparation method of the scratch-resistant BOPP matte film of Example 1.

[0123] The total thickness of the film is 20 µm, the thickness of the upper surface matte layer 1 is 1.6 µm, the thickness of the middle core layer 2 is 17.6 µm, and the thickness of the lower surface layer 3 is 0.8 µm.

[0124] In this comparative example, the melt viscosity of the matte masterbatch is greatly increased, and the fluidity is significantly reduced, which makes the processing more difficult and the film is prone to breakage, affecting the smoothness of production and the matte effect of the matte film, and easily causing bright spots on the film surface.

[0125] Comparative Example 6

[0126] This comparative example provides a BOPP matte film, comprising an upper matte layer 1, an intermediate core layer 2 and a lower surface layer 3 arranged in sequence. The specific structure can be referred to Figure 1 .

[0127] The preparation method of each layer of resin of the BOPP matte film of this comparative example comprises the following steps:

[0128] Preparation of resin for the upper surface matte layer 1: 39wt% copolymerized polypropylene (melt index of 9g / 10min), 42wt% high-density polyethylene (melt index of 16g / 10min), 11wt% ethylene-octene block copolymer (melt index of 7g / 10min, hard segment of 10wt% (ethylene accounts for 85wt%, octene accounts for 15wt%); soft segment of 90wt% (ethylene accounts for 30wt%, octene accounts for 70wt%)), 8wt% slightly cross-linked polypropylene (melt index of 3g / 10min, cross-linking degree of 3%) are uniformly mixed to obtain the resin for the upper surface matte layer.

[0129] Preparation of the middle core layer 2 resin: 99.5 wt % homopolymer polypropylene (melt index is 3 g / 10 min) and 0.5 wt % antistatic agent masterbatch are uniformly mixed to obtain the core layer resin.

[0130] Preparation of the resin for the lower surface layer 3: 99.5 wt % of homopolymer polypropylene (melt index is 3 g / 10 min) and 0.5 wt % of anti-blocking agent masterbatch are uniformly mixed to obtain the resin for the lower surface layer.

[0131] The preparation method of the BOPP matte film of this comparative example is the same as the preparation method of the scratch-resistant BOPP matte film of Example 1.

[0132] The total thickness of the film is 20 µm, the thickness of the upper surface matte layer 1 is 1.6 µm, the thickness of the middle core layer 2 is 17.6 µm, and the thickness of the lower surface layer 3 is 0.8 µm.

[0133] The matte film prepared in this comparative example has low impact strength, is easily brittle, and is easily broken by stretching, which affects the smoothness of production and the matte effect of the matte film.

[0134] Comparative Example 7

[0135] This comparative example provides a BOPP matte film, comprising an upper matte layer 1, an intermediate core layer 2 and a lower surface layer 3 arranged in sequence. The specific structure can be referred to Figure 1 .

[0136] The preparation method of each layer of resin of the BOPP matte film of this comparative example comprises the following steps:

[0137] Preparation of resin for the upper surface matte layer 1: 39wt% copolymerized polypropylene (melt index of 9g / 10min), 42wt% high-density polyethylene (melt index of 16g / 10min), 11wt% ethylene-octene block copolymer (melt index of 0.2g / 10min, hard segment of 60wt% (ethylene accounts for 85wt%, octene accounts for 15wt%), soft segment of 40wt% (ethylene accounts for 30wt%, octene accounts for 70wt%)), 8wt% slightly cross-linked polypropylene (melt index of 3g / 10min, cross-linking degree of 3%) are uniformly mixed to obtain the resin for the upper surface matte layer.

[0138] Preparation of the middle core layer 2 resin: 99.5 wt % homopolymer polypropylene (melt index is 3 g / 10 min) and 0.5 wt % antistatic agent masterbatch are uniformly mixed to obtain the core layer resin.

[0139] Preparation of the resin for the lower surface layer 3: 99.5 wt % of homopolymer polypropylene (melt index is 3 g / 10 min) and 0.5 wt % of anti-blocking agent masterbatch are uniformly mixed to obtain the resin for the lower surface layer.

[0140] The preparation method of the BOPP matte film of this comparative example is the same as the preparation method of the scratch-resistant BOPP matte film of Example 1.

[0141] The total thickness of the film is 20 µm, the thickness of the upper surface matte layer 1 is 1.6 µm, the thickness of the middle core layer 2 is 17.6 µm, and the thickness of the lower surface layer 3 is 0.8 µm.

[0142] In this comparative example, due to the poor melt fluidity of the matte masterbatch, the processing difficulty and energy consumption are increased, the smoothness of production is affected, the matte effect is affected, and bright spots are easily seen on the film surface.

[0143] Comparative Example 8

[0144] This comparative example provides a BOPP matte film, comprising an upper matte layer 1, an intermediate core layer 2 and a lower surface layer 3 arranged in sequence. The specific structure can be referred to Figure 1 .

[0145] The preparation method of each layer of resin of the BOPP matte film of this comparative example comprises the following steps:

[0146] Preparation of resin for the upper surface matte layer 1: 39wt% copolymerized polypropylene (melt index of 9g / 10min), 42wt% high-density polyethylene (melt index of 16g / 10min), 11wt% ethylene-octene block copolymer (melt index of 3g / 10min, hard segment of 30wt% (ethylene accounts for 85wt%, octene accounts for 15wt%), soft segment of 70wt% (ethylene accounts for 30wt%, octene accounts for 70wt%)), 8wt% slightly cross-linked polypropylene (melt index of 7g / 10min, cross-linking degree of 0.2%) are uniformly mixed to obtain the resin for the upper surface matte layer.

[0147] Preparation of the middle core layer 2 resin: 99.5 wt % homopolymer polypropylene (melt index is 3 g / 10 min) and 0.5 wt % antistatic agent masterbatch are uniformly mixed to obtain the core layer resin.

[0148] Preparation of the resin for the lower surface layer 3: 99.5 wt % of homopolymer polypropylene (melt index is 3 g / 10 min) and 0.5 wt % of anti-blocking agent masterbatch are uniformly mixed to obtain the resin for the lower surface layer.

[0149] The preparation method of the BOPP matte film of this comparative example is the same as the preparation method of the scratch-resistant BOPP matte film of Example 1.

[0150] The total thickness of the film is 20 µm, the thickness of the upper surface matte layer 1 is 1.6 µm, the thickness of the middle core layer 2 is 17.6 µm, and the thickness of the lower surface layer 3 is 0.8 µm.

[0151] Comparative Example 9

[0152] This comparative example provides a BOPP matte film, comprising an upper matte layer 1, an intermediate core layer 2 and a lower surface layer 3 arranged in sequence. The specific structure can be referred to Figure 1 .

[0153] The preparation method of each layer of resin of the BOPP matte film of this comparative example comprises the following steps:

[0154] Preparation of resin for the upper surface matte layer 1: 39wt% copolymerized polypropylene (melt index of 9g / 10min), 42wt% high-density polyethylene (melt index of 16g / 10min), 11wt% ethylene-octene block copolymer (melt index of 3g / 10min, hard segment of 30wt% (ethylene accounts for 85wt%, octene accounts for 15wt%), soft segment of 70wt% (ethylene accounts for 30wt%, octene accounts for 70wt%)), 8wt% slightly cross-linked polypropylene (melt index of 1g / 10min, cross-linking degree of 7%) are uniformly mixed to obtain the resin for the upper surface matte layer.

[0155] Preparation of the middle core layer 2 resin: 99.5 wt % homopolymer polypropylene (melt index is 3 g / 10 min) and 0.5 wt % antistatic agent masterbatch are uniformly mixed to obtain the core layer resin.

[0156] Preparation of the resin for the lower surface layer 3: 99.5 wt % of homopolymer polypropylene (melt index is 3 g / 10 min) and 0.5 wt % of anti-blocking agent masterbatch are uniformly mixed to obtain the resin for the lower surface layer.

[0157] The preparation method of the BOPP matte film of this comparative example is the same as the preparation method of the scratch-resistant BOPP matte film of Example 1.

[0158] The total thickness of the film is 20 µm, the thickness of the upper surface matte layer 1 is 1.6 µm, the thickness of the middle core layer 2 is 17.6 µm, and the thickness of the lower surface layer 3 is 0.8 µm.

[0159] The performance test results of the BOPP matte films of Examples 1 to 4 and Comparative Examples 1 to 9 are shown in Table 2 below.

[0160] Table 2

[0161]

[0162] From the above performance test data, we can know that:

[0163] The upper matte layer of the BOPP matte film of Comparative Example 1 does not contain ethylene-octene block copolymer and slightly cross-linked polypropylene, and the yield strength and tensile properties of the film surface are poor; the upper matte layer of the BOPP matte film of Comparative Example 2 does not contain slightly cross-linked polypropylene. Since the matte masterbatch lacks the cross-linked network formed between the molecular chains of the slightly cross-linked polypropylene, the film surface yield strength is low, the toughness is poor, and the resistance to external force when deformed by external force is low; the upper matte layer of the BOPP matte film of Comparative Example 3 does not contain ethylene-octene block copolymer, lacks the low octene in the ethylene-octene block copolymer. The hard segment with high octene content and the soft segment with high octene content have poor compression modulus, deformation resistance and toughness when the film surface is under pressure; the amount of micro-crosslinked polypropylene added in the upper surface matte layer of the BOPP matte film of Comparative Example 4 is greater than 10wt%, the molecular chains of the micro-crosslinked polypropylene are excessively crosslinked, the steric hindrance increases, the molecular chains are difficult to disperse stress during stretching, the tensile strength and yield strength decrease, and the scratch resistance of the film is reduced; the amount of ethylene-octene block copolymer added in Comparative Example 5 is greater than 14wt%, the molecular chains are entangled with each other, which is not conducive to the dispersion of high-density polyethylene in the copolymerized polypropylene, thereby affecting The hard segment content of the ethylene-octene block copolymer in the upper surface matt layer of the BOPP matt film of Comparative Example 6 is too low, the molecular chain is easy to slip when compressed, the compression modulus is low, the deformation is large, the molecular chain entanglement and cross-linking are weak when impacted, the impact strength is low, it is easy to crack, the scratch resistance is poor, and the matt effect is not good; the hard segment content of the ethylene-octene block copolymer in the upper surface matt layer of the BOPP matt film of Comparative Example 7 is too high, the hard segment plays a dominant role, the crystal size is too large and causes phase separation, destroys the uniformity, is not conducive to light scattering, and leads to uneven matt; The crosslinking degree of the micro-crosslinked polypropylene of Example 8 is less than 1%. The micro-crosslinked polypropylene has few crosslinking points, and the molecular chain is free. When stretched, the entanglement with the copolymerized polypropylene molecular chain is weak, easy to slip and displace, and the force cannot be effectively transmitted. The tensile and yield strengths are low, and it is easy to deform and break; the crosslinking degree of the micro-crosslinked polypropylene of Example 9 is greater than 5%. The micro-crosslinked polypropylene has too many crosslinking points, which makes the molecular chain rigid too strong, greatly increases the viscosity of the system, limits the activity of the molecular chain during stretching, reduces flexibility and toughness, reduces tensile and yield strengths, and easily causes phase separation of the matting system, making the matting effect of the film unstable and locally uneven. Compared with the embodiments of the present application, the matting effect of the BOPP matting films of Examples 1 to 9 after scratching is not as good as the scratch-resistant BOPP matting film of the present application, and the scratch resistance is poor.

[0164] The scratch-resistant BOPP matte film of the present invention is prepared by adding 8-14wt% of ethylene-octene block copolymer and 6-10wt% of micro-crosslinked polypropylene into an upper surface matte layer; the ethylene-octene block copolymer comprises 20wt%-40wt% of a highly crystalline hard segment with a low octene content and 60wt%-80wt% of an amorphous soft segment with a high octene content; the ethylene-octene block copolymer has excellent compression deformation performance and high impact strength, thereby improving the indentation in the pressure application stage; the micro-crosslinked polypropylene has the characteristics of high tensile strength and high yield strength, thereby improving the wear in the sliding stage; through the synergistic effect of the two, the compression deformation performance and impact strength of the copolymerized polypropylene as well as the tensile strength and yield strength can be improved, the indentation in the pressure application stage and the wear in the sliding stage can be reduced, the scratch resistance of the upper surface matte layer of the matte film can be improved, and a certain matte effect can be ensured, so that the scratch-resistant BOPP matte film of the present invention can reduce scratches and damage caused by scratches on the film surface.

[0165] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and the present invention is also intended to include these modifications and modifications.

Claims

1. A scratch-resistant BOPP matte film, characterized in that: It comprises an upper surface matte layer, an intermediate core layer and a lower surface layer which are arranged in sequence; the upper surface matte layer comprises a matte masterbatch, and the matte masterbatch comprises 28-50wt% copolymerized polypropylene, 8-14wt% ethylene-octene block copolymer, 6-10wt% slightly cross-linked polypropylene and 30-50wt% high-density polyethylene; the intermediate core layer comprises homopolymerized polypropylene; the lower surface layer comprises a glossy layer or a matte layer; The ethylene-octene block copolymer comprises a hard segment with a low octene content and a soft segment with a high octene content; in the hard segment, ethylene accounts for 80wt% to 90wt%, and octene accounts for 10wt% to 20wt%; in the soft segment, ethylene accounts for 20wt% to 40wt%, and octene accounts for 60wt% to 80wt%; in the ethylene-octene block copolymer, the hard segment accounts for 20wt% to 40wt%, and the soft segment accounts for 60wt% to 80wt%; at 230° C. and a load of 2.16kg, the melt index of the ethylene-octene block copolymer is 1 to 5 g / 10min; The crosslinking degree of the micro-crosslinked polypropylene is 1-5%; the melt index of the micro-crosslinked polypropylene is 2-4 g / 10 min at 230° C. and under a load of 2.16 kg; the preparation method of the micro-crosslinked polypropylene is a peroxide crosslinking method, which specifically comprises the following steps: 98.5-99.4 wt% of copolymerized polypropylene, 0.5-1 wt% of a peroxide crosslinking agent DCP and 0.1-0.5 wt% of an antioxidant are fully and uniformly mixed in a high-speed mixer, the mixed materials are added into a twin-screw extruder, heated and melted for extrusion, and the micro-crosslinked polypropylene is obtained through strand drawing, cooling, drying, pelletizing, vibrating screening and packaging.

2. The scratch-resistant BOPP matte film according to claim 1, characterized in that: The copolymerized polypropylene in the upper surface matte layer is one or more of ethylene-propylene binary copolymerized polypropylene or ethylene-propylene-butylene terpolymer; the melt index of the copolymerized polypropylene in the upper surface matte layer is 6-12 g / 10 min at 230° C. and a load of 2.16 kg; the melt index of the high-density polyethylene in the upper surface matte layer is 12-20 g / 10 min at 190° C. and a load of 21.6 kg.

3. The scratch-resistant BOPP matte film according to claim 1, characterized in that: The intermediate core layer further comprises 0.5-1 wt% of antistatic agent masterbatch; the homopolymer polypropylene of the intermediate core layer has a melt index of 2-4 g / 10 min at 230° C. and a load of 2.16 kg.

4. The scratch-resistant BOPP matte film according to claim 1, characterized in that: The lower surface layer is a glossy layer comprising 99-99.5wt% homopolypropylene and 0.5-1wt% anti-blocking agent masterbatch or a matte layer comprising 52wt% copolymer polypropylene and 48wt% high-density polyethylene; at 230°C and a load of 2.16kg, the homopolypropylene melt index of the glossy layer is 2-4g / 10min.

5. A method for preparing the scratch-resistant BOPP matte film according to any one of claims 1 to 4, characterized in that: The following steps are involved: The raw materials of the upper surface matte layer, the middle core layer and the lower surface layer are weighed in a dry ratio and then added to each extruder. The raw materials of each layer are melted and plasticized in each extruder and then metered by a metering pump. Then, according to different extruder flow channels, they are merged at a T-die to form a thick sheet. After the thick sheet is extruded, it is chilled and cast. After the cast sheet is shaped, it first enters the longitudinal stretching zone for longitudinal stretching and then enters the transverse stretching zone for transverse stretching. After the biaxial stretching of the film is completed, it is trimmed, corona treated, rolled, and aged, and finally cut and packaged to obtain the finished product.

6. The method for preparing the scratch-resistant BOPP matte film according to claim 5, characterized in that: The extrusion temperature of the upper surface matte layer is 230~255℃; the extruder temperature of the middle core layer and the lower surface layer is 250~260℃; the temperature of the T-die is 230~245℃, the temperature of the chilled roller is 30~35℃, the temperature of the longitudinal stretching preheating roller is between 128~145℃, the temperature of the longitudinal stretching zone is 120~135℃, the longitudinal stretching ratio is 4~5 times, the transverse stretching preheating temperature is 160~175℃, the temperature of the transverse stretching zone is 155~165℃, and the transverse stretching ratio is 7~9 times.

Citation Information

Patent Citations

  • High-intensity scraping-resistant polypropylene modified resin

    CN103524976A

  • BOPP matt film and preparation method thereof

    CN118849585A

  • Synthetic leather

    US20240173945A1